2021
DOI: 10.3390/foods10081704
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Diffusion Microextraction (GDME) Combined with Derivatization for Assessing Beer Staling Aldehydes: Validation and Application

Abstract: In this work, a gas-diffusion microextraction (GDME) methodology was optimized and validated for the analysis of selected staling aldehydes (furfural (FURF), 2-methylpropanal (2-MP), 2-methylbutanal (2-MB), 3-methylbutanal (3-MB), and acetaldehyde (ACET)) during natural and forced aging of beer. The methodology was optimized considering time, temperature of extraction, and derivatizing agent. Using 4-hydrazinobenzoic acid (HBA) as a derivatizing agent, the performance of the method was evaluated by assessing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Each sample was analysed in duplicate (antioxidant dose combinations and presence or absence of bentonite on fermentation). Duplicates are indeed enough, since according to recently published works with comparable matrices (Almeida Santos et al, 2020;Ferreira et al, 2021;Saracino et al, 2021;Pereira et al, 2021;Ferreira et al, 2022) results showed that duplicates instead of triplicates do not jeopardize the associated error of the measurement and the resulted error for both cases was very similar. This fact allows to perform more analysis by time unit promoting the throughput of samples, an important issue in routine analysis, when needed.…”
Section: Volatile Organic Compounds Identificationmentioning
confidence: 86%
“…Each sample was analysed in duplicate (antioxidant dose combinations and presence or absence of bentonite on fermentation). Duplicates are indeed enough, since according to recently published works with comparable matrices (Almeida Santos et al, 2020;Ferreira et al, 2021;Saracino et al, 2021;Pereira et al, 2021;Ferreira et al, 2022) results showed that duplicates instead of triplicates do not jeopardize the associated error of the measurement and the resulted error for both cases was very similar. This fact allows to perform more analysis by time unit promoting the throughput of samples, an important issue in routine analysis, when needed.…”
Section: Volatile Organic Compounds Identificationmentioning
confidence: 86%
“…Three mobile phases were tested: (i) acetonitrile (A) and water (B); (ii) acetonitrile (A) and 0.1% formic acid (B); and (iii) acetonitrile (A) and 10 mmol L −1 ammonium acetate buffer (B). The gradient elution method used in this study was adapted from a previous work [27,30] and was as follows: 50% to 65% A from 0 to 20 min, 65% to 100% A from 20 to 45 min, 100% to 50% A from 45 to 55 min, and 50% A from 55 to 60 min. The flow rate was set at 0.450 mL min −1 , the sample volume injected was 20 µL, and the detection was performed at 360 nm.…”
Section: Hplc Methods Optimizationmentioning
confidence: 99%
“…For preliminary tests, the gradient elution method used for this study was adapted from a previous work [27,30]. However, due to the changes introduced in the mobile phase and chromatographic column, certain derivatized carbonyl compounds co-elute when using these conditions.…”
Section: Hplc Methods Optimizationmentioning
confidence: 99%
“…GDME exhibits high sensitivity, when coupled with sensitive detection methods like GC-MS or high-performance liquid chromatography-ultraviolet (HPLC-UV). This empowers the quantification of tracelevel compounds in food analyses [10,48,[54][55][56][57][58][59][60][61][62].…”
Section: Gdme (Figurementioning
confidence: 99%
“…This extraction process utilized a derivative solution containing 3 g DNPH in 100 mL of water-acetonitrile (1:1) at pH 2.0. Optimal conditions were established, involving the use of 10 mL of beer and 750 µL of the derivative solution as the acceptor phase, with extraction for 5 min at 30 • C. Aldehyde-DNPH derivatives were analyzed using HPLC-UV, and the presence of these aldehydes was confirmed using HPLC-APCI-MS. Conversely, Ferreira et al [55] focused on the simultaneous extraction of 2-methyl butanal, 2-methyl propanal, 3-methyl butanal, acetaldehyde, and furfural from beer. They evaluated various parameters affecting the extraction process, such as time, temperature, derivatizing agent (DNPH and HBA), and two extraction approaches (headspace or immersed module).…”
Section: Pacheco Et Al (2010) Demonstrated the Effectiveness Of Gdme ...mentioning
confidence: 99%